Marine sponges maintain stable bacterial communities between reef sites with different coral to algae cover ratios. Issue 9 (5th August 2021) - Campana, Sara; Demey, Celine; Busch, Kathrin; Hentschel, Ute; Muyzer, Gerard; de Goeij, Jasper M
ABSTRACT: Marine sponges play a major ecological role in recycling resources on coral reef ecosystems. The cycling of resources may largely depend on the stability of the host–microbiome interactions and their susceptibility to altered environmental conditions. Given the current coral to algal phase shift on coral reefs, we investigated whether the sponge-associated bacterial communities of four sponge species, with either high or low microbial abundances (HMA and LMA), remain stable at two reefs sites with different coral to algae cover ratios. Additionally, we assessed the bacterial community composition of two of these sponge species before and after a reciprocal transplantation experiment between the sites. An overall stable bacterial community composition was maintained across the two sites in all sponge species, with a high degree of host-specificity. Furthermore, the core bacterial communities of the sponges remained stable also after a 21-day transplantation period, although a minor shift was observed in less abundant taxa (< 1%). Our findings support the conclusion that host identity and HMA–LMA status are stronger traits in shaping bacterial community composition than habitat. Nevertheless, long-term microbial monitoring of sponges along with benthic biomass and water quality assessments are needed for identifying ecosystem tolerance ranges and tipping points in ongoing coral reef phase shifts. Abstract : Analysis of four different sponge holobionts reveals that their associated bacterial communities are host-specific and remain stable across habitats with different coral to algae cover ratios.